Rapid Detection and Differentiating of the Predominant Salmonella Serovars in Chicken Farm by TaqMan Multiplex Real-Time PCR Assay - Xin, Suhua; Zhu, Hong; Tao, Chenglin; Zhang, Beibei; Yao, Lan; Zhang, Yaodong; Afayibo, Dossêh Jean Apôtre; Li, Tao; Tian, Mingxing; Qi, Jingjing; Ding, Chan; Yu, Shengqing; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Salmonella has been known as an important zoonotic pathogen that can cause a variety of diseases in both animals and humans. Poultry are main reservoir for the Salmonella serovars Salmonella Pullorum (S. Pullorum), Salmonella Gallinarum (S. Gallinarum), Salmonella Enteritidis (S. Enteritidis) and Salmonella Typhimurium (S. Typhimurium). The conventional serotyping methods for differentiating Salmonella serovars are complicated, time-consuming, laborious and expensive, therefore rapid and accurate molecular diagnostic methods are needed for effective detection and prevention of contamination. This study developed and evaluated a TaqMan multiplex real-time PCR assay for simultaneous detection and differentiation of the S. Pullorum, S. Gallinarum, S. Enteritidis and S. Typhimurium. In results, the optimized multiplex real-time PCR assay was highly specific and reliable for all four target genes. The analytical sensitivity corresponded to 3 colony forming unit (CFU) for these four Salmonella serovars, respectively. The detection limit for the multiplex real-time PCR assay in artificially contaminated samples was 500 CFU/g without enrichment, while 10 CFU/g after pre-enrichment. Moreover, the multiplex real-time PCR was applied to the poultry clinical samples, which achieved comparable results to the traditional bacteriological examination. Taken together, these results indicated that the optimized TaqMan multiplex real-time PCR assay will be a promising tool for clinical diagnostics and epidemiologic study of Salmonella in chicken farm and poultry products.